Catalytic performance of Cu- and Zr-modified beta zeolite catalysts in the methylation of 2-methylnaphthalene - Fatih Güleç (KeAi Communications Co., Ltd., 2018)
Abstract 2,6-Dimethylnaphthalene (2,6-DMN) is a commercially important chemical for the production of polyethylenenaphthalate and polybutylene naphthalate. However, its complex synthesis procedure and high production cost significantly reduce the use of 2,6-DMN. In this study, the synthesis of 2,6-DMN was investigated with methylation of 2-methylnaphthalene (2-MN) over metal-loaded beta zeolite catalysts including beta zeolite, Cu-impregnated beta zeolite and Zr-impregnated beta zeolite. The experiments were performed in a fixed-bed reactor at atmospheric pressure under a nitrogen atmosphere. The reactor was operated at a temperature range of 400–500 °C and varying weight hourly space velocity between 1 and 3 h−1. The results demonstrated that 2,6-DMN can be synthesized by methylation of 2-MN over beta type zeolite catalysts. Besides 2,6-DMN, the product stream also contained other DMN isomers such as 2,7-DMN, 1,3-DMN, 1,2-DMN and 2,3-DMN. The activity and selectivity of beta zeolite catalyst were remarkably enhanced by Zr impregnation, whereas Cu modification of beta zeolite catalyst had an insignificant effect on its selectivity. The highest conversion of 2-MN reached 81%, the highest ratio of 2,6-DMN/2,7-DMN reached 2.6 and the highest selectivity of 2,6-DMN was found to be 20% by using Zr-modified beta zeolite catalyst.